Write the equation in the form y′=f(y/x) then use the substitution y=xu to find an implicit general solution. Then solve the initial value problem.


y′=5y2+4x2xy, y(1)=3


The resulting differential equation in x x and u u can be written as xu′= which is separable.

Separating variables we arrive at du=dx/x

Separating variables and and simplifying the solution can be written in the form u2+1=Cf(x) where C is an arbitrary constant and f(x)= .

Transforming back into the variables x and y and using the initial condition to find C we find the explicit solution of the initial value problem is y = .

Respuesta :

Looks like the ODE is supposed to be

[tex]y'=\dfrac{5y^2+4x^2}{xy}[/tex]

In that case, let [tex]y(x)=xu(x)[/tex], so that [tex]y'=xu'+u[/tex]. Substitute these into the ODE to get

[tex]xu'+u=\dfrac{5x^2u^2+4x^2}{x^2u}[/tex]

[tex]xu'=\dfrac{4u^2+4}u[/tex]

which is separable as

[tex]\dfrac u{u^2+1}\,\mathrm du=4x\,\mathrm dx[/tex]

Integrate both sides to get

[tex]\dfrac12\ln(u^2+1)=2x^2+C[/tex]

We can solve for [tex]u^2[/tex]:

[tex]\ln(u^2+1)=4x^2+C[/tex]

[tex]u^2+1=Ce^{4x^2}[/tex]

[tex]u^2=Ce^{4x^2}-1[/tex]

Replace [tex]u=\frac yx[/tex] to get the general solution,

[tex]\dfrac{y^2}{x^2}=Ce^{4x^2}-1[/tex]

Given that [tex]y(1)=3[/tex], we find

[tex]9=Ce^4-1\implies C=10e^{-4}[/tex]

so the particular solution is

[tex]\dfrac{y^2}{x^2}=10e^{4(x^2-1)}-1[/tex]

[tex]\implies y=\pm x\sqrt{10e^{4(x^2-1)}-1}[/tex]

The solution of this differential equation is [tex]y = \pm x \cdot \sqrt{49\cdot x^{10}-0.8}[/tex].

How to solve a non-linear differential equation

Now we proceed to write the differential equation in the form [tex]y'=f\left(\frac{y}{x} \right)[/tex]:

[tex]y' = \frac{5\cdot y^{2}+4\cdot x^{2}}{x\cdot y}[/tex] (1)

[tex]y' = 5\cdot \frac{y}{x}+4\cdot \frac{x}{y}[/tex]

If we know that [tex]u = \frac{y}{x}[/tex], then we have the following expression and separate the variables:

[tex]x\cdot u' = 5\cdot u + \frac{4}{u}[/tex]

[tex]\int {\frac{u}{5\cdot u^{2}+4} } \, du = \int {\frac{dx}{x} }[/tex]

If we apply the substitution [tex]k = 5\cdot u^{2}+4[/tex], then we have the following integral:

[tex]\frac{1}{10}\int {\frac{dk}{k} } = \int {\frac{dx}{x} }[/tex] (2)

And we solve it:

[tex]\frac{1}{10}\cdot \ln k = \ln x + C[/tex]

[tex]k = C\cdot e^{x^{10}}[/tex]

[tex]5\cdot u^{2}+4 = C\cdot x^{10}[/tex]

[tex]5\cdot \frac{y^{2}}{x^{2}} + 4 = C\cdot x^{10}[/tex]

[tex]5\cdot y^{2} = C\cdot x^{12}-4\cdot x^{2}[/tex]

Where [tex]C[/tex] is the integration constant.

If we know that [tex]x = 1[/tex] and [tex]y = 3[/tex], then the integration constant is:

[tex]5\cdot (3)^{2} = C\cdot (1)^{12}-4\cdot (1)^{2}[/tex]

[tex]C = 49[/tex]

And the solution of this differential equation is:

[tex]y = \pm x \cdot \sqrt{49\cdot x^{10}-0.8}[/tex] (3)

The solution of this differential equation is [tex]y = \pm x \cdot \sqrt{49\cdot x^{10}-0.8}[/tex]. [tex]\blacksquare[/tex]

Remark

The statement present mistakes and is poorly formatted. Correct form is described below:

Write the equation in the form [tex]y' = f\left(\frac{y}{x} \right)[/tex], then use the substitution [tex]y= x\cdot u[/tex] to find an implicit general solution. Then solve the initial value problem:

[tex]y' = \frac{5\cdot y^{2}+4\cdot x^{2}}{x\cdot y}[/tex] (1)

To learn more on differential equations, we kindly invite to check this verified question: https://brainly.com/question/25731911

ACCESS MORE